Predictors of Reduced Frequency of Physical Activity 3 Months After Injury: Findings From the Prospective Outcomes of Injury Study. Issue 12 (1st December 2016) - Harcombe, Helen; Samaranayaka, Ari; Derrett, Sarah
Abstract: Background: Physical inactivity is a risk factor for noncommunicable diseases. Incurring an injury has been identified as a barrier to physical activity. However, it is not known which factors, if any, are associated with reduced activity among general injury populations. Objective: The 2 study objectives were: (1) to investigate changes in physical activity frequency from before an injury to 3 months after the injury and (2) to examine the association of preinjury, injury-related, and postinjury factors with reduced physical activity frequency in participants with a range of injury types. Design: This was a cohort study. Methods: Participants (N=2, 856) who were 18 to 64 years of age were asked about preinjury demographic and health factors, injury-related factors, and postinjury factors. Data were collected through telephone interviewing (88%), a postal questionnaire (11%), and face-to-face interviewing (0.5%) 3 months after the injury. Results: Of the 2, 793 participants for whom complete physical activity data were available, 55% (n=1, 536) had reduced physical activity 3 months after the injury event. Preinjury and injury-related factors associated with a greater risk of reduced physical activity included living with non-family members; a lower extremity dislocation, sprain, or strain; and an injury with greater anatomical severity. Postinjury factors associated with reduced physical activity included greater disability, pain or discomfort, poor general health, not having returned to work, and having a worse-than-expected recovery 3 months after the injury. A large proportion (61%) of this cohort with injuries was seen by physical therapists. Limitations: Data collection was retrospective and based on participant recall. Conclusions: A large proportion of participants had reduced physical activity 3 months after the injury. Knowledge about preinjury, injury-related, and postinjury characteristics associated with reduced physical activity may help health care professionals identify people at risk of not returning to their preinjury physical activity frequency.